Integration of Religious and Ethical Foundations in Education: A Study of Curriculum Objectives and Content - Risky Oktafia; Erfina; Gunawan; Desty Natalia; Nandang Budiman (Journal of Practice Learning and Educational Development, 2026)
Education in Indonesia plays a strategic role in shaping students' character by strengthening religious and ethical foundations in the curriculum. This study aims to analyze the integration of religious and ethical values in the Merdeka Curriculum, particularly in terms of its objectives, content, and implementation in the context of arts education. The research method used literature study and policy analysis by examining academic sources and relevant education regulations. The results of the study show that the Merdeka Curriculum explicitly places the Pancasila Student Profile as the foundation for character building, with the dimensions of faith, devotion to God Almighty, and noble character as the main indicators. The integration of religious and ethical values is realized both through core subjects, such as Religious Education and Pancasila, and across disciplines through the Pancasila Student Profile Strengthening Project (P5). In arts education, these values are reflected through the use of local and religious-based artworks that contribute to strengthening students' moral awareness, ethics, and cultural identity. However, implementation in the field still faces challenges in the form of variations in teacher competence, differences in value interpretation, and limited supporting facilities. This study concludes that the integration of religious and ethical foundations in the Merdeka Curriculum plays an important role in shaping the character of students holistically, thus requiring a structured, contextual, and collaborative implementation strategy, especially in arts education.